Users’ perception of the OH-EpiCap evaluation tool based on its application to nine national antimicrobial resistance surveillance systems - Moura, Pedro; Collineau, Lucie; Sandberg, Marianne; Tomassone, Laura; De Meneghi, Daniele; Norström, Madelaine; Bennani, Houda; Häsler, Barbara; Colomb-Cotinat, Mélanie; Bourély, Clémence; Filippitzi, Maria-Eleni; Mediouni, Sarah; et al. (Frontiers in Public Health, 2023)
Antimicrobial resistance (AMR) surveillance systems involve multiple stakeholders and multilevel standard operating procedures, which increase in complexity with further integration of the One Health (OH) concept. AMR is a OH challenge. It is crucial for the success of an AMR surveillance system to evaluate its performance in meeting the proposed objectives, while complying with resource restrictions. The OH-EpiCap tool was created to evaluate the degree of compliance of hazard surveillance activities with essential OH concepts across there dimensions: organization, operational activities, and impact of the OH surveillance system. To present feedback on the application of the OH-EpiCap from a user’s perspective, the tool was used to evaluate nine national AMR surveillance systems, each with different monitoring contexts and objectives. The OH-EpiCap tool was assessed using the updated CoEvalAMR methodology. This methodology evaluates the content themes and functional aspects of the tool in a standardized way, while it also captures the user’s subjective experiences in using the tool via a strengths, weaknesses, opportunities, and threats (SWOT) approach. The results of the evaluation of the OH-EpiCap are presented and discussed. The OH-EpiCap is an easy-to-use tool, which can facilitate a fast macro-overview of the application of the OH concept to a surveillance activity, when used by specialists in the matter, serving as a basis for the discussion of possible adaptations of AMR surveillance activities, or targeting areas that may be further investigated using other pre-established tools.